Word Stress : Theoretical and Typological Issues - van der Hulst, Harry (Cambridge : Cambridge University Press, 2014)
Word stress has long presented challenges to phonologists, as they have sought to uncover patterns in its distribution, and devise models to account for its behaviour and formal representation both within single languages and cross-linguistically. In this collection, a team of world-renowned researchers present a variety of viewpoints on the methods and problems involved. Offering fresh perspectives on the topic and its study, this book is specifically concerned with basing theoretical work on broad typological surveys and focuses on the collection, selection and use of data in the analysis of word stress and word rhythm, including their phonetic manifestations. An extensive introduction presents a state-of-the-art review of stress research. The contributors also present StressTyp2, a project in an advanced stage of development, which intends to make publicly available information on word stress in a broad sample of languages and will offer new ways of understanding this key research area.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Linguistics